Increased epicardial tissue and reduced TAPSE and MAPSE scores in borderline personality disorders. Early indicators for cardiovascular risk? - Charlotte F. M. Schaefer; Britta Stapel; Nicole Scharn; Sebastian Bertele; Alexander Glahn; Kai G. Kahl; Phileas J. Proskynitopoulos; Mechthild Westhoff-Bleck (Frontiers in Psychiatry)
IntroductionLife expectancy of patients with borderline personality disorder (BPD) is reduced compared to the general population, which has been in part attributed to a heightened risk for cardiometabolic disorders. One prior study reported increased values of epicardial adipose tissue (EAT), which has been shown to be a sensitive marker for cardiovascular disease risk. Against this background, studies assessing cardiac function in patients with BPD have been missing to date.MethodsThe present study included 28 female patients with a diagnosis of BPD and 28 age, sex, and BMI-matched controls (mean age 29 ± 11 years). EAT thickness and parameters of cardiac function were assessed by echocardiography. Diabetes risk was assessed using the Finnish Diabetes Risk (FINDRISC) score, and metabolic syndrome was defined in accordance to National Cholesterol Education Program Adult Treatment Panel-III (NCEP/ATPIII) criteria. Additionally, self-report questionnaires were used to assess lifestyle factors, retrospectively reported childhood trauma and current symptoms of depression and anxiety.ResultsOur study confirmed significantly elevated levels of EAT in patients with BPD compared to controls. Additionally, significant decreases in right (TAPSE) and left (MAPSE) ventricular function, albeit within the normal range, were measured in BPD patients. Contrarily, left ventricular ejection fraction was similar in both groups. Further, patients with BPD reported high levels of childhood trauma and clinically relevant depression and anxiety symptoms. Diabetes risk and frequency of metabolic syndrome as well as serum levels of prognostic markers NT-proBNP and GDF15 were similar in both groups. BPD patients were more frequently smokers and reported lower levels of physical exercise compared to controls.ConclusionThe present study demonstrates morphological and functional differences in a matched sample of female patients with BPD and healthy controls, pointing to an increased risk for the development of cardiovascular disorders. These findings highlight the importance of screening for cardiovascular risk markers and of including interventions that aim to improve adverse life-style habits early on in the clinical management of BPD.